2013 Global hunger index: The challenge of hunger: Building resilience to achieve food and nutrition security - von Grebmer, Klaus; Headey, Derek D.; Olofinbiyi, Tolulope; Wiesmann, Doris; Yin, Sandra; Yohannes, Yisehac; Foley, Connell; von Oppeln, Constanze; Iseli, Bettina; Béné, Christophe; Haddad, Lawrence James (International Food Policy Research Institute, 2013)
The 2013 Global Hunger Index (GHI) report-the eighth in an annual series- presents a multidimensional measure of national, regional, and global hunger. It shows that the world has made some progress in reducing hunger since 1990, but still has far to go. The 2013 GHI report focuses on resilience in theory and in practice. The relief and development communities have long struggled to understand why some people fare better than others when confronting stresses or shocks. Given that world hunger remains “serious” according to the index, resilience-building efforts are much needed to help poor and vulnerable people cope with hunger seasons, droughts, and other natural and manmade disasters both short-term and long-term. Building resilience will involve boosting food and nutrition security. In order to achieve that goal, the humanitarian and development communities must work together.